Inovasi Metode Pembelajaran PAI Diera Digital - Ulin Nuha; Sohibul Barkah (Al-Khazin: Jurnal Pendidikan Agama Islam, 2025)
The transformation of education in the digital era requires the adaptation of PAI to remain relevant and effective in achieving its learning goals. This study focuses on three main aspects: (1) identifying the most relevant and effective forms of PAI learning method innovation applied at various levels of education (2) analyzing the challenges faced in the implementation of these innovations, including teacher readiness, availability of digital infrastructure, and relevance of content; and (3) formulate the right strategy to develop the professional competence of PAI teachers in mastering and implementing innovative methods based on digital technology. This research aims to analyze and map the innovation of Islamic Religious Education (PAI) learning methods in the digital era through a systematic literature study approach. The method used is literature review by analyzing a number of articles, books, and related scientific documents published in the last ten years. The results of the study show that the most prominent PAI method innovations include the use of blended learning technology, flipped classroom, mobile learning, and the integration of digital learning resources (e.g., interactive videos, game-based learning applications) to increase students' motivation and understanding of Islamic values. The main challenges identified are the digital divide between urban and rural schools, the lack of ongoing training for teachers, and the need to develop a curriculum that is adaptive to technological developments. As a solution, this study recommends a practice-oriented sustainable professional development strategy, strengthening collaboration between teachers, and equitable digital infrastructure procurement policies. The conclusion of this study emphasizes that the innovation of PAI learning methods in the digital era requires synergy between the readiness of human resources (teachers) and the availability of infrastructure and strong policy support.